Patogenisitas Fusarium oxysporum Endofit asal Gulma dari Pertanaman Pisang terhadap Bibit Pisang Raja Bulu - Wardhana, Vinsen Willi; Wiyono, Suryo; Hidayat, Sri Hendrastuti; Widodo, Widodo (Jurnal Fitopatologi Indonesia, 2021)
Pathogenicity of Endophytic Fusarium oxysporum Isolated from Weeds in Banana Plantations against Bananas Seedlings var. Raja BuluFusarium oxysporum is known as the causal agent of wilt disease and caused severe damages in banana plantations around the world. It was reported earlier that weeds grown around banana plants harboroud F. oxysporum as endophyte. These endophytes may become source of disease inoculum for banana plants.  Research was carried out to isolate and identify endophytic F. oxysporum from weed’s roots around banana plants in Bogor, West Java and further determine its pathogenicity. Observation on morphological characteristic involved colony, conidia and chlamydospores. Pathogenicity test of endophyte isolates in the laboratory was conducted using plantlets of banana var. Raja Bulu.  F. oxysporum was successfully isolated from 9 weed species that grew around banana plants.  All isolates showed morphological characteristics of F. oxysporum, i.e. purple colonies, three septate canoe macroconidia, cylindrical and kidney microconidia and often reveal chlamydospores singly. All of the isolates were pathogenic on var. Raja Bulu causing 100 % disease incidence and severity of 58.33 to 77.78 % and 50.00 to 69.44 % of leaf wilting and corm necrosis, respectively.